Race, Place, and Context: The Persistence of Race Effects in Traffic Stop Outcomes in the Face of Situational, Demographic, and Political Controls. (November 2020) - Shoub, Kelsey; Epp, Derek A.; Baumgartner, Frank R.; Christiani, Leah; Roach, Kevin
Abstract: Evidence that racial minorities are targeted for searches during police traffic stops is widespread, but observed differences in outcomes following a traffic stop between white drivers and people of color could potentially be due to factors correlated with driver race. Using a unique dataset recording over 5 million traffic stops from 90 municipal police departments, we control for and evaluate alternative explanations for why a driver may be searched. These include: (1) the context of the stop itself, (2) the characteristics of the police department including the race of the police chief, and (3) demographic and racial composition of the municipality within which the stop occurs. We find that the driver's race remains a robust predictor: black male drivers are consistently subjected to more intensive police scrutiny than white drivers. Additionally, we find that all drivers are less likely to be subject to highly discretionary searches if the police chief is black. Together, these findings indicate that race matters in multiple and varied ways for policing outcomes.